2022
DOI: 10.1021/acs.langmuir.1c02342
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Additives on the Electrochemical and Interfacial Properties of SiOx-Based Anode Materials for Lithium–Sulfur Batteries

Abstract: The influence of electrolyte additives on the electrochemical and interfacial properties of SiO x -based anodes for lithium–sulfur batteries (Li–S) was systematically investigated. Four different electrolyte additives, namely, lithium nitrate, vinylene carbonate (VC), vinyl ethylene carbonate, and fluoroethylene carbonate (FEC), were added to the bare electrolyte comprising 1 M LiTFSI in tetraethylene glycol dimethyl ether/1,3 dioxolane in a ratio of 1:1 (v/v). The self-extinguishing time (SET) of the liquid e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…After contacting lithium with the polymer electrolyte, a passivation layer formed, and it was possible to identify differences in the composition of this thin film compared with the native film. The deconvoluted C 1s spectrum showed peaks at 292.5, 289.20, 286.3, 284.2, and 282.2 eV, which are assigned to C–F, CO, C–O, C–C, and Li–C, respectively. , The F 1s spectrum showed that the peak at 688.4 eV represents C–F. In the Li 1s spectrum, the peak centered at 54.70 eV could be assigned to lithium hydroxide or alkoxide. , In the O 1s spectrum, the peaks observed at 528.9, 531.1, and 532.6 eV are assigned respectively to metal oxides, metal carbonates, and carbonyl or CO bonds.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…After contacting lithium with the polymer electrolyte, a passivation layer formed, and it was possible to identify differences in the composition of this thin film compared with the native film. The deconvoluted C 1s spectrum showed peaks at 292.5, 289.20, 286.3, 284.2, and 282.2 eV, which are assigned to C–F, CO, C–O, C–C, and Li–C, respectively. , The F 1s spectrum showed that the peak at 688.4 eV represents C–F. In the Li 1s spectrum, the peak centered at 54.70 eV could be assigned to lithium hydroxide or alkoxide. , In the O 1s spectrum, the peaks observed at 528.9, 531.1, and 532.6 eV are assigned respectively to metal oxides, metal carbonates, and carbonyl or CO bonds.…”
Section: Resultsmentioning
confidence: 97%
“…The C–C bond obtained at 284.2202 eV (Figure ) has been considered as a reference for further plotting. The curves were fitted using 90% of Gaussian and 10% of Lorentzian Voigt peak shapes . An electron flood gun was used to neutralize the charge …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 3a, the signals of elements F and S appear, which indicated that the fluoride emulsion and EDOT were successfully doped. Moreover, the high‐resolution C 1s spectrum analysis showed that the peak located at 291.9 eV and 287.1 eV was assigned to C−F [12] and C−S [13] bonds, respectively. The test results also demonstrated that fluorine‐containing emulsion and EDOT were successfully doped in the modified PMIA membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Energy storage devices are an essential part of the energy supply system. Advanced secondary batteries can meet large-scale energy storage needs, such as lithium-ion batteries (LIBs) , and lithium–sulfur (Li–S) batteries, which can store and utilize clean energy . LIB is one of the best-performing batteries, and it has been successfully applied to portable electronic products, such as mobile communication equipment, notebook computers, and digital cameras. , Li–S battery is one of the new secondary batteries, because S demonstrates a remarkable theoretical capacity (1675 mAh g –1 ). , …”
Section: Introductionmentioning
confidence: 99%